Goethe, the Lyrist 100 Poems in New Translations Facing the Originals with a Biographical Introduction - Zeydel, Edwin H. (UNC Studies in the Germanic Languages and Literatures, 1955)
In this volume originally published in 1955, Zeydel provides English translations of one hundred of Goethe's poems divided into nine periods. The biographical introduction traces Goethe's development as seen in his poems and an appendix gives information on musical settings to the poems.